2020
DOI: 10.1371/journal.pone.0228735
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylceramide synthase maintains influenza virus entry and infection

Abstract: Influenza virus is an enveloped virus wrapped in a lipid bilayer derived from the host cell plasma membrane. Infection by influenza virus is dependent on these host cell lipids, which include sphingolipids. Here we examined the role of the sphingolipid, glucosylceramide, in influenza virus infection by knocking out the enzyme responsible for its synthesis, glucosylceramide synthase (UGCG). We observed diminished influenza virus infection in HEK 293 and A549 UGCG knockout cells and demonstrated that this is att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 53 publications
5
22
0
Order By: Relevance
“…In this study we demonstrate that the GCS inhibitors GZ-161 and GZ-346 have a broad spectrum Previous works showed that knocking out UGCG (the gene encoding for GCS) impaired the entry of Influenza virus by endocytosis (43). In addition to its role in endocytosis, the cellular membrane has a major role in establishing specialized membrane replication compartments (RCs) that are critical sites for the synthesis of the viral genome (44).…”
Section: Discussionmentioning
confidence: 68%
“…In this study we demonstrate that the GCS inhibitors GZ-161 and GZ-346 have a broad spectrum Previous works showed that knocking out UGCG (the gene encoding for GCS) impaired the entry of Influenza virus by endocytosis (43). In addition to its role in endocytosis, the cellular membrane has a major role in establishing specialized membrane replication compartments (RCs) that are critical sites for the synthesis of the viral genome (44).…”
Section: Discussionmentioning
confidence: 68%
“…It was recently shown that Ugcg knockout cells demonstrate a reduction in the replication of the respiratory RNA virus Influenza A virus, a member of the family Orthomyxoviridae ( 22 ). Thus, we further examined the antiviral activity of GCS inhibitors against Influenza A virus.…”
Section: Resultsmentioning
confidence: 99%
“…In this study we demonstrate that the GCS inhibitors GZ-161 and GZ-346 inhibit viral replication of SARS-CoV-2. The importance of glycosphingolipids biosynthesis in viral life cycle was demonstrated recently for Influenza virus and severe fever with thrombocytopenia syndrome virus (SFTSV) ( 22 , 23 ). Moreover, iminosugars are known for their broad-spectrum antiviral activity, presumably due to their mechanism of action as endoplasmic reticulum (ER)-resident α-glucosidases I and II inhibitors ( 24 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Influenza virus induces GlcCer elevation [40,41] (Fig. 1), which seems to be important for viral life cycle since the suppression of the SL biosynthesis pathway results in the inhibition of the maturation of influenza virus particles [42][43][44]. In addition, ceramide glucosyltransferase (UGCG, GlcCer synthase) inhibitors have a broad antiviral activity against RNA viruses of different genus: neuroinvasive Sindbis virus (SVNI), West Nile virus (WNV), influenza A virus, and SARS-CoV-2.…”
Section: Associated Infectious Diseasesmentioning
confidence: 99%